Families with young children during the COVID-19 pandemic—The importance of family type, perceived partnership roles, parental stress, and social support for changes in the home learning environment during lockdown - Prokupek, Luisa; Cohen, Franziska; Oppermann, Elisa; Anders, Yvonne (Frontiers in Psychology, 2023)
Beginning in March 2020, the lockdown precipitated by the Covid-19 pandemic resulted in many challenges, especially for families with young children. Many children had little or no access to institutional education. Therefore, they were even more dependent on their parents providing them with home learning activities (HLA) to support their development. We examined the adaptability of families with regard to changes in parents’ provision of HLA in traditional two-parent families, single parent families, and large families compared to before the lockdown. We focused on family resources, such as a supportive distribution of roles within the partnership, or social support, as predicting factors of adaptability in N=8513 families with children aged 18-69 months. Additionally, we considered parental stress as a further influencing factor. The cross-sectional data depicts families from a nationwide online survey, which we conducted during spring 2020 in Germany. We found that all three family types offered their children more learning activities at home, albeit with slight differences between the families. However, we identified differences in the factors influencing families’ adaptability: Across all family types, we found slight to medium negative relations between adaptability and parental stress. The relations were most evident in large families. Furthermore, social support exhibits somewhat positive relations to the adaptability of large families. For adaptability in single-parent families, gender differences were initially evident. Among single fathers, the change in parental HLA was stronger than among single mothers. However, this relation disappeared when we took parental stress and social support into account. For traditional two-parent families and single parents, our analyses revealed barely significant relations between the investigated predictors and changes in HLA during lockdown. Overall, our study confirms that high stress limits the adaptability of providing HLA in families and that social support mitigates negative relations between stress and the provision of HLA, especially in large families. In order to develop effective and needs-based family support programmes, it is therefore important to help parents cope with stress and provide them with low-threshold social support. The extent to which these services need to be adapted to different family types must be surveyed in more depth.